Evaluasi Kapabilitas Tata Kelola Teknologi Informasi menggunakan Kerangka Kerja COBIT 5 Domain APO13 dan DSS05 (Studi pada Dinas Komunikasi dan Informatika Kota Batu) - Carlo Julio Caesarrieva; Andi Reza Perdanakusuma; Widhy Hayuhardhika Nugraha Putra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Departement of Communication and Informatics (KOMINFO) Batu City is an public office under the auspices of Government of Batu city which to serve society to provide planning, manage and to coordinate on information technology that needed by citizen. The problem that Agency of Agency of Communication and Informatics (KOMINFO) has are lack of planning on Technology information governance. Capability level is measured to give information about the condition of governance technology information which using APO13 (Manage Security) and process DSS05 (Manage Security Services) this measurement scale from level 0 Incomplete process to level 5 Optimized process and is based on evidence to give detailed information about the condition .Based on this research result the Departement of Communication and Informatics (KOMINFO) Batu City has obtained capability level on APO13 (Manage Security) at third level (level 3) and on DSS05 (Manage Security Services) at first level (level 1). Gap level function is to provide the correct improvement for Departement of Communication and Informatics (KOMINFO) Batu. On APO13 the Gap level had been obtained from targeted level at two levels. On DSS05 the gap level based on gap analysis is by four levels. The recommendation based on this research are to complete documentation plan about technology information policy, provide some standard procedure to every activity in technology information and to control the performance of IT Governance.